Social Mobility Trends in Canada: Going up the Great Gatsby Curve - Marie Connolly; Catherine Haeck; David Lapierre (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2019)
While cross-sectional increases in inequality are a cause for concern, the study of the intergenerational transmission of socioeconomic status is perhaps more relevant. How is social status reproduced from one generation to the next? Recent work has highlighted the relationship, if not causal then correlational, between inequality and measures of social mobility in a cross-country setting. This relationship is dubbed the Great Gatsby Curve (Corak 2013): places with higher inequality during one's childhood are correlated with lower intergenerational income mobility between the child and his or her parents. In this paper, newly developed administrative Canadian tax data are exploited to compute measures of intergenerational income mobility at the national and provincial levels. This work provides detailed descriptive evidence on the trends in social mobility. Results show that mobility has steadily declined over time, and that there has been an increase in the inequality of the parental income distribution, as measured by the Gini coefficient. Hence Canada, and all its provinces, have been "going up" the Great Gatsby Curve. The cross sectional, cross country relationship thus also holds within a same country over time, leading credence to the more causal than correlational nature of the relationship, though causality is not formally tested here. The decrease in mobility, particularly for children born in the bottom quintile of the income distribution, should be of concern to federal and provincial policymakers alike and highlights the need for additional research in order to provide equal opportunities to all children.
Keywords: J62; D63; 330; social mobility; intergenerational transmissions; income inequality; Great Gatsby curve; Canada